2013
DOI: 10.7575/aiac.ijalel.v.3n.1p.152
|View full text |Cite
|
Sign up to set email alerts
|

Verb-Noun Collocation Proficiency and Academic Years

Abstract: Generally vocabulary and collocations in particular have significant roles in language proficiency. A collocation includes two words that are frequently joined concurrently in the memory of native speakers. There have been many linguistic studies trying to define, to describe, and to categorise English collocations. It contains grammatical collocations and lexical collocations which include nouns, adjectives, verbs, and adverb. In the context of a foreign language environment such as Iran, collocational profic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…When compared to the use of typical (structured) exercises, the study's technique appears to have extraordinary value in developing the natural and spontaneous employment of collocations. It also endorses findings from Ebrahimi-Bazzaz, Abd Samad, Bin Ismail, and Noordin (2014) that verb-noun collocational knowledge may be developed more quickly and easily when taught in formal educational settings as this study indicates. This further confirms a study by Zhang and Sukying (2021) on the impact of many exposures in the incremental process of vocabulary learning by indicating that the growth of collocational knowledge depends on the number of contacts with the target words in context .…”
Section: Lexical Rangesupporting
confidence: 89%
“…When compared to the use of typical (structured) exercises, the study's technique appears to have extraordinary value in developing the natural and spontaneous employment of collocations. It also endorses findings from Ebrahimi-Bazzaz, Abd Samad, Bin Ismail, and Noordin (2014) that verb-noun collocational knowledge may be developed more quickly and easily when taught in formal educational settings as this study indicates. This further confirms a study by Zhang and Sukying (2021) on the impact of many exposures in the incremental process of vocabulary learning by indicating that the growth of collocational knowledge depends on the number of contacts with the target words in context .…”
Section: Lexical Rangesupporting
confidence: 89%
“…This is perhaps because the fourth-year learners have more experience in learning vocabulary knowledge, which is consistent with previous findings suggesting that understanding the aspects of vocabulary knowledge requires sufficient language experience (e.g., Hayashi & Murphy, 2011;Schmitt & Zimmerman, 2002, Nontasee & Sukying, 2021a. Diao (2004) also found that senior students showed better collocation competence than freshmen students, likely due to the senior students having more exposure to English, and other studies have also reported that students' knowledge of collocations improves through their academic years (Al-Zahrani 1998;Ebrahimi-Bazzaz et al, 2014;Gitsaki, 1999). The results also indicate that, overall, collocational competence for both first-and fourth-year students is unsatisfactory and students showed poor collocational knowledge in general.…”
Section: Thai University Learners' Receptive and Productive Knowledge Of Lexical Collocationsmentioning
confidence: 96%